(untitled) (Research, Society and Development, 2022)
Tobacco consumption through hookah by the young population has increased in recent years in Brazil. In this study, we sought to identify the prevalence of consumption and the profile of hookah users among dentistry students. This is a research with a quantitative approach, carried out through self-administered questionnaires addressing the smoking habit and knowledge about hookah. 160 academics enrolled in the Dentistry course at the State University of Paraná (UNIOESTE) in 2016 agreed to participate in the study. According to the data collected, 69% (n=111) of the academics interviewed had already tried the hookah. 59% (n=66) of these started using between 17 and 19 years old and 41% (n=45) between 20 and 24 years old. For 45% (n=50) of the participants in this study, curiosity was responsible for the contact with the hookah, and for 23% (n=25) being at the university provided the use of this substance. The influence of friends motivated 77% to try the hookah, and the association of this type of tobacco with illicit drugs was reported by 8% (9/111) of the participants. Regarding the knowledge of academics on the subject, 52% (n=83) said they believed that, unfortunately, cigarette smoke has more toxic substances when compared to hookah. Thus, the findings emphasize the need to investigate and develop better ways to make students aware of the components found or produced by this type of tobacco and the diseases associated with this practice.